The Effect of CSR, Fixed Asset Intensity, Profitability and Leverage On Tax Avoidance with Institutional Ownership as A Moderating Variable - Rahmawaty, Nita; Dwi Astuti, Christina (Devotion : Journal of Research and Community Service, 2023)
In this study, the authors are interested in examining how corporate social responsibility, fixed asset intensity, profitability, and leverage influence tax evasion with institutional ownership as a moderating variable. The population of all manufacturing companies in the property & real estate sector and the building construction sector listed on the Indonesia Stock Exchange from 2018 to 2021 totaling 110 populations, according to the criteria required in this study there are only 21 companies as samples for 2018 to with 2021. The results show that Corporate Social Responsibility has no effect on tax avoidance, while the intensity of fixed assets, profitability, leverage, has a positive effect on tax avoidance partially. For the moderating variable institutional ownership is not able to strengthen the effect of Corporate Social Responsibility on tax avoidance, and institutional ownership is not able to weaken the positive effect of profitability on tax avoidance, but institutional ownership can weaken the positive effect of fixed asset intensity and leverage on tax avoidance